2017
DOI: 10.15171/ijoem.2017.958
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Antibiotics of Bacteria Exposed to Gamma Radiation Emitted from Hot Soils of the High Background Radiation Areas of Ramsar, Northern Iran

Abstract: Background: Over the past several years our laboratories have investigated different as-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…This is may be due to the overexpression of proteins after expoure to γ-radiation. The results of the present study agreed with Mortazavi et al (2017) who reported that there were significant reductions in bacterial susceptibility to antibiotics especially in K. pneumoniae after exposure to γ-radiation with with inhibition zone 20.3mm of and 14.7mm, respectively. Quantitative RT-PCR was performed as a sensitive method to quantify the gene expression of dnak and groES that quickly translated to Dnak and GroeS proteins as reported by vanghele et al (2016).…”
Section: Resultssupporting
confidence: 92%
“…This is may be due to the overexpression of proteins after expoure to γ-radiation. The results of the present study agreed with Mortazavi et al (2017) who reported that there were significant reductions in bacterial susceptibility to antibiotics especially in K. pneumoniae after exposure to γ-radiation with with inhibition zone 20.3mm of and 14.7mm, respectively. Quantitative RT-PCR was performed as a sensitive method to quantify the gene expression of dnak and groES that quickly translated to Dnak and GroeS proteins as reported by vanghele et al (2016).…”
Section: Resultssupporting
confidence: 92%
“…A highly significant dose effect was observed at 2 kGy for all or some of the tested antibiotics depending on the isolates. It was found [16] that gamma radiation emitted from the hot soil of the high background radiation areas was capable of making significant alterations in the pathogen bacterial susceptibility to antibiotics that differ with different bacterial isolates. Others [45,48] reported that radiation induced reactive oxygen species upon water radiolysis affecting the membrane permeability of ionic channels in the bacterial cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing radiation can inactivate microorganisms through direct photons energy hit on the main target (DNA) or indirectly through the production of highly reactive oxygen and hydroxyl radicals through splitting of water molecules within the product and the resident bacteria [15], leading to disruption of microbial cell membranes, protein structures, and nucleic acids. In addition, gamma radiation can enhance the susceptibilities of foodborne pathogenic bacteria to antibiotics [16]. This study aims at employing Charm II system for rapid detection of tetracycline and streptomycin in fresh local beef tissue (meat and liver) samples, isolating and identifying the relevant highly antibiotic resistant bacteria, with attempt to increase their sensitivity to those antibiotics using gamma radiation.…”
Section: Introductionmentioning
confidence: 99%
“…“Stress factors experienced during space include microgravity, sleep deprivation, radiation, isolation, and microbial contamination, all of which can promote immune suppression (1, 2). Under these conditions, the risk of infection from opportunistic pathogens increases significantly, particularly during long-term missions (3). If infection occurs, it is important that the infectious agent should not be antibiotic resistant.…”
Section: Lettermentioning
confidence: 99%
“…My colleagues and I have previously shown that exposure to both ionizing (3) and nonionizing (4) electromagnetic radiation can make bacteria more resistant to antibiotics (the so-called “bacterial adaptive response”). The adaptive response can be defined as increased resistance in living organisms preexposed to a low-level stressor (e.g., low doses of ionizing radiation) before exposure to a highly challenging stressor (5).…”
Section: Lettermentioning
confidence: 99%